Eksegesis Matius 5:14-16 dalam Perspektif Identitas Para Murid Yesus - Okyob Jeon; Yasti Tiran (STT Pelita Dunia, 2023)
Abstract: The Sermon on the Mount is the first of five critical discourses in the Gospel of Matthew. When reading the Sermon on the Mount, several scholars have emphasized the importance of δικαιοσύνη (righteousness) as well as identity formation or community building. In particular, the salt and light metaphor in 5:13-16 is one of the texts that describes the identity of the disciples. Therefore, this study read Matthew 5:14-16 again from the perspective of discipleship identity. The method used in this research is qualitative research that focuses more on exegetical studies. The results of the study are as follows. In verse 14a, Jesus declared His disciples’ identity, which is light-bearers. In verses 14b-15, he showed them the clear and vivid influence around them. In verse 16, his disciples’ mission is explained; disciples as light-bearers must definitely practice good works so that others will glorify God. In particular, the disciples of this age, who are young seminarians and servants of God, must live out God's truth through living with integrity, be faithful disciples of Jesus and do good deeds with love for believers and those who do not know Jesus. Abstrak: Khotbah di Bukit merupakan yang pertama dari lima ajaran signifikan dalam Injil Matius. Ketika membaca Khotbah di Bukit, beberapa ahli telah menekankan pentingnya δικαιοσύνη (kebenaran) dan pembentukan identitas atau pembangunan komunitas. Secara khusus, metafora garam dan terang dalam 5:13-16 adalah salah satu teks yang menggambarkan identitas para murid. Oleh karena itu, penelitian ini melihat 5:14-16 dari perspektif identitas para murid Yesus. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif yang lebih menitikberatkan pada studi eksegesis. Hasil dari penelitian ini adalah sebagai berikut. Dalam ayat 14a, Yesus menyatakan identitas murid-murid-Nya, yaitu sebagai pembawa terang. Dalam ayat 14b-15, Ia menunjukkan pengaruh yang jelas dan nyata di sekitar mereka. Dalam ayat 16, misi murid-murid-Nya dijelaskan; murid-murid sebagai pembawa terang harus melakukan perbuatan baik agar orang lain memuliakan Allah. Secara khusus, murid-murid pada zaman ini, yang merupakan seminaris muda dan hamba-hamba Tuhan, harus menghidupi kebenaran Allah yang ditunjukkan melalui sikap hidup yang berintegritas, menjadi murid Yesus yang setia dan melakukan perbuatan baik dengan kasih kepada orang percaya maupun yang belum mengenal Yesus.